How to measure the motivations of sports volunteers in Poland? First stage of the study with the Polish adaptation and validation of the VMS-ISE - Mateusz Rozmiarek; Mateusz Grajek; Karolina Sobczyk; Magdalena Król-Zielińska (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background The study aimed to adapt to Polish conditions and validate the seven-factor Volunteer Motivation Scale for International Sporting Events (VMS-ISE) as one of the tools used to measure volunteer motivation at international sports events. Methods The study used a diagnostic survey method. The sample consisted of 78 volunteers– 36 women and 43 men with a mean age of 24.8 years (± 5.6 years). To assess the reliability of the Polish version of the questionnaire, measurements were conducted in a two-week test-retest. Results The CFA result showed that the chi-square test was not significant (χ2 = 8.541, p = 0.231), indicating an acceptable fit of the items in each factor. The reliability of the internal consistency of the factors was tested by examining Cronbach’s alpha scores for each motivation dimension, which ranged from 0.72 to 0.86, with a mean value of 0.77, meeting the recommended criterion. Construct validity was confirmed for all factors– AVEs ranged from 0.58 to 0.84, with a mean value of 0.70, exceeding the cut-off point. Of all the scale factors, all correlations except Interpersonal Contacts and Patriotism showed a statistically significant relationship (p < 0.05), indicating that the factors were satisfactorily distinct from each other and represented correctly prepared constructs. In addition, all factors except Love of Sport showed statistically significant correlations in terms of the studied socio-demographic characteristics (p < 0.05). Conclusions The obtained result indicates that the Polish adaptation of the questionnaire (called VMS-ISE.PL), after applying the necessary procedures, is characterized by satisfactory psychometric indices and can be used to study the motivation of sports volunteers in Poland.